The Coronavirus diseases 2019 (Covid-19) pandemic: literature review - Kurniati, Niqmatul (Research of Environmental Science and Engineering, 2020)
The end of 2019 or early 2020, the world was shocked by the outbreak of new pneumonia in Wuhan, China, which then spread rapidly throughout the world. This outbreak is named coronavirus disease 2019 (COVID-19). COVID-19 is the name given by the World Health Organization (WHO) for patients with Covid-19. This disease's etiology is known for certain, which is included in the ribonucleic acid virus (RNA), namely a new type of Coronavirus, beta corona. Viruses and one group with the Coronavirus cause severe acute respiratory middle east respiratory syndrome (MERS CoV) and syndrome (SARS). Symptoms of Covid-19 can be mild to severe associated with the respiratory disease with common symptoms of fever, cough, and shortness of breath. COvid-19 is very dangerous for those who have comorbidities such as chronic bronchitis, emphysema, heart failure, or diabetes, which will have a more serious impact that can lead to death. Therefore, we conducted a review of studies related to Covid-19, which were widely applied in early 2020 to the end of August 2020.